The Migration of Free Roman Citizens and a Barbarian King to Histria: Origins, Status, Rights, and Professions - Starac, Alka (Pnyx: Journal of Classical Studies, 2022)
This paper examines the migration and origins of Roman citizens in Histria based mainly on epigraphical sources. It focuses on the origins and identity of the newcomers who settled permanently in the region during the entire Imperial period. It looks into free individuals who migrated voluntarily in search of a better life and trade earnings, and others who settled as veterans or found refuge in Histria from troubles in their homeland. The legal status of settlers, visitors, and immigrants was resolved by special decisions, as evidenced by the inscription on the use of thermal baths near Buje, which records the decurions' permission to the colonists, incolae, and foreigners to bathe. Inscriptions confirm various types of migration in Histria, seasonal, temporary, and permanent. Members of the municipal aristocracy and Augustals retained their status after the relocation. Several veterans, mostly born in Italy, settled permanently in Histria. Particularly interesting is the case of Rasparaganus, King of the Sarmatian tribe of Roxolani, who died and was buried with his family on the small island in Pola. Among migrants without ties to the military or the administration but who came to Histria because of their profession or in search of higher earnings, clothing merchants stand out. Temporary visitors were registered in important religious and health centres. Finally, the paper examines city patrons coming from another city to establish whether they can be considered migrants.